Design and Bulk Sensitivity Analysis of a Silicon Nitride Photonic Biosensor for Cancer Cell Detection - Prasanna Kumaar S.; Sivabramanian A. (International Journal of Optics)
Bulk sensitivity is an important parameter to validate the efficiency of the photonic waveguide sensor. Due to recent advancements in point-of-care silicon photonic biosensing, the focus is to identify the effective way to improve sensitivity. Integrating polydimethylsiloxane (PDMS) microfluidic channel in sensor architecture decreases the sensitivity due to leakage of molecules at edges. The silicon nitride (SiN4) Mach–Zehnder interferometer utilizes the refractive index of different cancer cells (1.39–1.401) to determine the bulk sensitivity. The proposed gradient step rib-slot structure of 970 nm wide and 400 nm thickness is designed to hold the liquid sample without any PDMS material. This novel waveguide exhibits high waveguide bulk sensitivity Sw,bulk and device bulk sensitivity Sd compared with the gradient rib waveguide. We achieved a waveguide bulk sensitivity Sw,bulk of 2.0699 RIU/RIU and device sensitivity Sd of 568 nm/RIU through finite-difference time-domain (FDTD) analysis.